A descriptive Study of Infrastructure Capabilities for Digital Records Preservation among Selected Public Institutions in Tanzania - Daniel, Jacquiline; Ndumbaro, Faraja (University of Dar es Salaam Library Journal, 2022)
In this paper, results of a descriptive study on institutional infrastructure capabilities for preserving digital records are presented. The study was carried out at Records and Archives Management Department (RAMD) and Registration, Insolvency and Trusteeship Agency (RITA). Informing the study, two research questions were in consideration: How capable are RAMD and RITA in terms of infrastructure capabilities for preserving digital records? What infrastructural challenges RAMD and RITA contend in preserving digital records? A multiple case studies and mixed research approaches were used. The study population comprised of 290 staff members, 75 from RAMD and 215 from RITA. A sample of 74 middle and lower level officers and 13 senior staff were purposively and randomly selected respectively. Data were collected through key informant ' s face to face interview and questionnaire. Results indicate that RAMD and RITA have relatively advanced infrastructure capabilities. Notably, shortage of fund, inadequate hardware, insufficient IT support, inadequate management commitment towards enhancement of infrastructure capabilities are among the digital records preservation challenges faced by RAMD and RITA. Based on the results, would seem to suggest that RAMD and RITA are at transitional capabilities because the available infrastructures are advance but inadequate to effectively support digital records preservation initiatives.